2012
DOI: 10.15288/jsad.2012.73.794
|View full text |Cite
|
Sign up to set email alerts
|

Direct and Indirect Effects of Impulsivity Traits on Drinking and Driving in Young Adults

Abstract: ABSTRACT. Objective: Impulsivity is strongly associated with alcohol-related risk-taking behavior, and this association has been found to be mediated by alcohol cognitions. The current study expanded this literature by comparing the relative association of distinct impulsivity traits with a specifi c risky behavior-drinking and driving. We then tested whether drinking-and-driving expectancies uniquely mediated this relation over and above other cognitions about alcohol and drinking and driving. Method: College… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
23
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 42 publications
2
23
0
Order By: Relevance
“…Our results are consistent with partial mediation, suggesting that elevated demand confers unique risk for drinking and driving, independent of the drinking-and-driving-related cognitions we examined. More generally, these findings are consistent with the broader literature suggesting that cognitive factors serve to connect distal risk factors to engagement in risky behaviors such as drinking and driving (e.g., LaBrie et al, 2012;Treloar et al, 2012). The finding that drinking drivers have greater perceived safe driving limits is consistent with the limited number of studies in this area (Gulliver & Begg, 2004;Royal, 2003).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Our results are consistent with partial mediation, suggesting that elevated demand confers unique risk for drinking and driving, independent of the drinking-and-driving-related cognitions we examined. More generally, these findings are consistent with the broader literature suggesting that cognitive factors serve to connect distal risk factors to engagement in risky behaviors such as drinking and driving (e.g., LaBrie et al, 2012;Treloar et al, 2012). The finding that drinking drivers have greater perceived safe driving limits is consistent with the limited number of studies in this area (Gulliver & Begg, 2004;Royal, 2003).…”
Section: Discussionsupporting
confidence: 87%
“…have been linked to engagement in drinking and driving, including favorable attitudes toward drinking and driving (McCarthy et al, 2007;McCarthy & Pedersen, 2009), knowledge of drinking-and-driving laws (Sloan et al, 2014), and impulsivity (Rossow, 2008;Sloan & Eldred, 2015;Sloan et al, 2014;Treloar et al, 2012). Although this research has advanced our understanding of risk factors for drinking and driving, there is a need for more integrative models specifying the determinants of drinking and driving in order to ultimately improve interventions.…”
Section: S Everal Individual Difference Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study the percentage of the drunk drivers were calculated from the whole test groups, which could make some difference between the results [33].…”
Section: Discussionmentioning
confidence: 96%
“…Empirical studies have demonstrated that perceiving drinking and driving as more dangerous is associated with reduced odds of doing so (Grube and Voas 1996; McCarthy et al 2007; Bingham et al 2007; McCarthy and Pedersen 2009; Fairlie et al 2010). Perceived risk of drinking and driving also uniquely predicts driving after drinking (Bingham et al 2007), and has been found to mediate the influence of impulsive personality traits on drinking and driving (Treloar et al 2012). Together, this research suggests that perceived danger is an important precursor to the intention to drive after drinking.…”
mentioning
confidence: 99%